Cotton-based room-temperature phosphorescent material as well as preparation method and application thereof
By grafting the degreased cotton with the benzeneboric acid derivative and combining with the aqueous phase B-O click chemical reaction, a room temperature phosphorescent material based on cotton was prepared, which solved the problems of complex preparation of existing materials and environmental pollution, and achieved efficient and environmentally friendly preparation of phosphorescent material.
Patent Information
- Application Number
- CN202510275634.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing phosphorescent materials require the use of toxic reagents during the preparation process, and the preparation of most organic materials is complex and time-consuming, and the polymer matrix is difficult to degrade, resulting in environmental pollution.
By grafting the degreased cotton with the benzeneboric acid derivative and combining with the aqueous phase B-O click chemical reaction, a room temperature phosphorescent material based on cotton was prepared, and the water resistance of the material was improved through physical adsorption and chemical grafting.
A room temperature phosphorescent material with a long life and high quantum yield has been prepared, and the material has good waterproof properties, and can restore phosphorescence emission by heating after being eroded by water, and has high reusability.
Smart Images

Figure CN119777152A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phosphorescent materials, and in particular to a cotton-based room temperature phosphorescent material and a preparation method and application thereof. Background Art
[0002] Phosphorescence is a slow photoluminescence phenomenon, which is characterized by the continued existence of the luminescence phenomenon when the excitation light is stopped. It has the advantages of long luminescence lifetime, large Stokes shift, and diverse excitation properties. In recent years, room temperature phosphorescent (RTP) materials with long lifetime have been widely studied due to their broad application prospects in anti-counterfeiting, sensing, information encryption, and bio-imaging. Narrowing the energy gap between the excited singlet state (S1) and the triplet state (Tn), increasing the intergap crossing rate (ISC), increasing the spin-orbit coupling (SOC), and stabilizing triplet emission are the core elements to improve RTP performance.
[0003] At present, researchers have developed many design methods to improve the RTP performance of phosphorescent materials, such as improving SOC by introducing halogen bonds, aromatic carbonyls or heavy metal atoms into the structure of RTP materials, thereby promoting the ISC process; or suppressing the energy loss of non-radiative decay through host-guest interactions, hydrogen bond interactions, crystal engineering, and constructing porous organic frameworks. Among them, polymer room temperature phosphorescent materials have attracted much attention due to their good processability, easy synthesis, and thermal stability. The polymer matrix can protect the phosphor from the influence of oxygen in various ways to suppress the non-radiative decay of triplet excitons, and the phosphor and polymer can suppress the vibration and rotation of the phosphor through various interactions such as hydrogen bonds, covalent bonds, and ionic bonds. However, most organic materials need to be prepared through complex and time-consuming chemical processes, and a large amount of toxic reagents often need to be added during the reaction process. The polymer matrix used needs to be refined and is difficult to degrade. Therefore, the development of new natural polymer RTP materials to solve the above problems is of great significance for the practical application of room temperature phosphorescent materials and the reduction of environmental pollution. Summary of the invention
[0004] The main purpose of the present invention is to provide a cotton-based room temperature phosphorescent material and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides a method for preparing a cotton-based room temperature phosphorescent material, comprising the following steps: subjecting absorbent cotton and a phenylboronic acid derivative to a grafting reaction to obtain a grafted product.
[0006] Furthermore, the phenylboronic acid derivative is selected from any one of 4-carboxyphenylboronic acid, 4,4'-biphenyldiboronic acid, 4-biphenylboronic acid, and 4'-bromo-4-biphenylboronic acid.
[0007] Furthermore, the operation process of the grafting reaction is: immersing absorbent cotton in deionized water, adding a tetrahydrofuran solution of a phenylboronic acid derivative, then adding ammonia water, and then stirring at 80° C. for 1 hour, and finally filtering and drying to obtain the room temperature phosphorescent material.
[0008] Furthermore, the mass ratio of the cotton wool to 4-carboxyphenylboric acid is 100:4, and the mass ratio of the cotton wool to 4,4'-biphenyldiboric acid or 4-biphenylboric acid or 4'-bromo-4-biphenylboric acid is 100:1.
[0009] The main component of cotton is cellulose, a natural polymer material. Cotton contains a large number of evenly arranged hydroxyl groups, which not only provide a strong hydrogen bond network, inhibit non-radiative transitions and promote the excitons to return from the triplet state to the ground state, but are also easily modified by other functional groups. Although cellulose has a weak phenomenon of aggregation-triggered emission, it is difficult to observe in cotton, and this weak intrinsic luminescence can hardly meet the actual production and life needs.
[0010] The present invention synthesizes a series of room temperature phosphorescent materials through a water-based BO click chemistry reaction, hydrogen bond interactions between boric acid molecules and cotton wool, and the rigid structure of the cotton wool. In an alkaline environment, small boric acid molecules are easily reacted with hydroxyl groups in cotton wool in an aqueous phase or other common solvents to form borate ester bonds. Under hydrogen bond interactions and a rigid environment, the movement of the boric acid chromophore is suppressed, the intersystem crossing (ISC) process is enhanced, and thus phosphorescence emission is promoted. Multicolor room temperature phosphorescence emission can be achieved by selecting phenylboronic acid derivatives with different structures to tune the degree of conjugation of boric acid molecules.
[0011] Furthermore, before the grafting reaction, the absorbent cotton is subjected to oxidation treatment and reduction treatment in sequence.
[0012] Furthermore, the operation process of the oxidation treatment is: adding absorbent cotton and sodium periodate into deionized water, reacting at 60° C. in the dark for 10 hours, then adding ethylene glycol to stop the reaction, and finally dialyzing, filtering, and drying.
[0013] Furthermore, the reduction treatment process is as follows: adding the oxidized absorbent cotton and sodium borohydride into deionized water, stirring at room temperature for 4 hours, and finally dialyzing, centrifuging, and drying.
[0014] Furthermore, the mass ratio of the absorbent cotton to sodium periodate and sodium borohydride is 2.58:3.21:8.
[0015] Although cellulose contains a large number of hydroxyl groups, its solubility in water is relatively poor. The present invention adopts a directional oxidation-reduction technology, using sodium periodate to selectively oxidize the two secondary hydroxyl groups at the second and third positions on the glucose ring of cotton fiber, and then reducing the oxidized hydroxyl groups with sodium borohydride, which can greatly increase the water solubility and reactivity of hydroxyl groups, enhance the activity of hydroxyl groups at specific sites on the absorbent cotton, and greatly enhance the lifespan and quantum yield of room temperature phosphorescent materials.
[0016] Furthermore, after obtaining the grafted product, the grafted product is subjected to silicone oil adsorption or silanol grafting treatment.
[0017] Furthermore, the operation process of the silicone oil adsorption is: soaking the grafted product in amino silicone oil for 2 hours, and then taking it out for drying; The operation process of the silanol grafting treatment is: adding n-octyltriethoxysilane to a mixture of ethanol and water, hydrolyzing to form silanol, then adding the grafted product to react for 2 hours, and finally taking it out for heating and drying treatment.
[0018] Furthermore, the volume ratio of ethanol to water is 9:1.
[0019] The present invention combines the room temperature phosphorescent material with silicone oil and silane by means of physical adsorption and chemical grafting, thereby improving the water resistance of the material.
[0020] Room temperature phosphorescent materials are usually easily quenched by oxygen and water. Since cotton constructs a micro-rigid environment, it resists the interference of oxygen to a certain extent, but it is greatly affected by water. Amino silicone oil emulsion can form a protective layer on the surface of cotton, effectively blocking water penetration and improving the waterproof performance of the product. Octyltriethoxysilane is hydrolyzed into silanol in a mixed solution of ethanol and water, and forms hydrogen bonds with the hydroxyl groups on the surface of cotton, and self-crosslinks between molecules to form a polysiloxane network. After heating, it can be stably grafted on the cotton surface, reducing the surface free energy and producing a hydrophobic interface, which can also enhance the waterproofness of the material.
[0021] The present invention also provides a room temperature phosphorescent material based on cotton, which is prepared according to the above preparation method.
[0022] The present invention also provides application of the cotton-based room temperature phosphorescent material in preparing ink or coating.
[0023] The beneficial effects of the present invention are embodied in: The present invention is the first to use natural material absorbent cotton to prepare a variety of room temperature phosphorescent materials. The longest life of the materials reaches 1.04 seconds, and they have a long afterglow emission after the ultraviolet lamp is turned off.
[0024] The invention can adjust the afterglow color by controlling the conjugation degree of grafted phenylboronic acid, and the product has excitation light wavelength dependence, and its phosphorescence emission range can be changed by changing the excitation light wavelength.
[0025] The present invention enhances the water resistance of the room temperature phosphorescent material by physical adsorption and chemical grafting. The material has long-term stability, can restore its phosphorescent emission by heating after being corroded by water, and has high reusability.
[0026] The room temperature phosphorescent material of the present invention can be made into ink or coating, written on materials such as gauze, and can be applied to the fields of anti-counterfeiting and smart textiles.
[0027] The invention uses natural polymer materials as the matrix, the raw materials are low-cost and green and environmentally friendly, water is used as the main solvent, the preparation process is simple, and it has wide adaptability and broad development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The fluorescence and phosphorescence spectra of M1.
[0029] Figure 2 The fluorescence and phosphorescence spectra of M2.
[0030] Figure 3 The fluorescence and phosphorescence spectra of M3.
[0031] Figure 4 The fluorescence and phosphorescence spectra of M4.
[0032] Figure 5 The fluorescence and phosphorescence spectra of M5.
[0033] Figure 6 It is a structural characterization diagram of the material (in the figure, a is the infrared spectrum of different components and the subtraction spectrum of M5 and modified cotton, b is the X-ray diffraction spectrum of absorbent cotton and modified cotton, c is the X-ray electron energy spectrum carbon spectrum, d is the X-ray electron energy spectrum boron spectrum).
[0034] Figure 7 Scanning electron microscope and application photos of the material (in the figure, Figure a is a scanning electron microscope of cotton wool, Figure b is a scanning electron microscope of M2, Figure c, Figure e, and Figure g are photos of ink made by writing M5 with a brush on gauze under natural light, irradiated by 365nm ultraviolet lamp, and under 254nm ultraviolet lamp for 2s and then turned off, Figure d, Figure f, and Figure h are photos of ink made by injecting M5 with a syringe on gauze under natural light, irradiated by 365nm ultraviolet lamp, and under 254nm ultraviolet lamp for 2s and then turned off).
[0035] Figure 8Phosphorescence spectra of M2 at the initial stage, after water vapor fumigation for 5 minutes, and after drying in a 100°C drying oven for 2 minutes and 4 minutes.
[0036] Fig. 9 The waterproof comparison phosphorescence spectra of the materials (in the figure, Figure a is the phosphorescence emission spectra of M6 and M6 soaked in water, Figure b is the phosphorescence emission spectra of M7 and M7 soaked in water, and Figure c is the phosphorescence emission spectra of M5 and M5 soaked in water).
[0037] Fig.10 The phosphorescence spectra of M1 under different excitation wavelengths. DETAILED DESCRIPTION
[0038] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0039] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial channels or can be obtained by existing known methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods known to those skilled in the art. Among them: 4-carboxyphenylboric acid (98%) was purchased from Anage reagent platform. 4,4'-biphenyldiboric acid (>95%) and 4'-bromo-4-biphenylboric acid (97%) were purchased from Aladdin reagent platform. 4-Biphenylboric acid (98%), sodium periodate (99.5%), and n-octyltriethoxysilane (97%) were purchased from McLean reagent platform. Sodium borohydride (NaBH4) and ethylene glycol were purchased from Sinopharm Chemical Reagent Co., Ltd. Aminosilicone oil, model 8040A, cas: 28323-47-9, was purchased from Guangzhou Xinguan Chemical Technology Co., Ltd. Degreased cotton, i.e. cotton with fat removed, was purchased from Caoxian Weiguang Sanitary Materials Co., Ltd.
[0040] Example 1 Preparation of cotton-based room temperature phosphorescent material M1 Disperse 0.1 g of absorbent cotton in 10 ml of deionized water, add 1 ml of 10 mg / ml 4-carboxyphenylboronic acid (CBa) tetrahydrofuran solution, then add 1 ml of 25 wt% ammonia water, stir at 80 ° C and 640 r / min for 1 hour, then filter and dry the residue at -0.1 MPa and 80 ° C for 12 hours to obtain a grafted product, which is the cotton-based room temperature phosphorescent material M1.
[0041] Example 2 Preparation of cotton-based room temperature phosphorescent material M2 The preparation method of this embodiment is the same as that of Example 1, except that the tetrahydrofuran solution of 4-carboxyphenylboronic acid (CBa) is replaced with a tetrahydrofuran solution of 4,4'-biphenyldiboronic acid (Bp-dBa) with a concentration of 1 mg / ml. The final grafted product is the cotton-based room temperature phosphorescent material M2.
[0042] Example 3 Preparation of cotton-based room temperature phosphorescent material M3 The preparation method of this embodiment is the same as that of Embodiment 1, except that the tetrahydrofuran solution of 4-carboxyphenylboronic acid (CBa) is replaced by a tetrahydrofuran solution of 4-biphenylboronic acid (BpBa) with a concentration of 1 mg / ml. The final grafted product is the cotton-based room temperature phosphorescent material M3.
[0043] Example 4 Preparation of cotton-based room temperature phosphorescent material M4 The preparation method of this embodiment is the same as that of Example 1, with the only difference being that the tetrahydrofuran solution of 4-carboxyphenylboronic acid (CBa) is replaced with a tetrahydrofuran solution of 4'-bromo-4-biphenylboronic acid (BrBpBa) with a concentration of 1 mg / ml, and the final grafted product is the cotton-based room temperature phosphorescent material M4.
[0044] Example 5 Preparation of cotton-based room temperature phosphorescent material M5 The preparation method of this embodiment is the same as that of embodiment 2, except that the absorbent cotton is replaced with modified cotton; The preparation method of the modified cotton is as follows: 2.58g of absorbent cotton and 3.21g of sodium periodate are added to 100ml of deionized water, reacted at 60°C in the dark for 10h, 10ml of ethylene glycol is added to stop the reaction, and then the reaction mixture is put into a dialysis bag with a molecular weight cutoff of 8000, and dialyzed at room temperature for 12h with pure water as a dialysate to remove impurities, and the process is repeated three times, and finally the dialyzed reaction mixture is filtered, and the obtained filter residue is dried at room temperature and vacuum degree of -0.1Mpa for 12h to obtain the oxidized absorbent cotton; Take 1.5g of oxidized absorbent cotton and dissolve it in 30ml of deionized water, add 0.8g of sodium borohydride, stir and react at room temperature and 640r / min for 4h, then put the reaction mixture into a dialysis bag with a molecular weight cutoff of 8000, dialyze with pure water as the dialysis fluid at room temperature for 12h to remove impurities, repeat three times, and finally centrifuge the dialyzed reaction mixture at 6000r / min. The centrifuged product is dried at room temperature and vacuum degree of -0.1Mpa for 12h to obtain modified cotton.
[0045] The final grafted product is the cotton-based room temperature phosphorescent material M5.
[0046] Example 6 Preparation of cotton-based room temperature phosphorescent material M6 The preparation method of this embodiment is the same as that of Example 5, with the only difference being that after obtaining the grafted product, the grafted product is subjected to silicone oil adsorption treatment. The specific operation process is as follows: 0.1 g of the grafted product is soaked in 5 g of amino silicone oil for 2 h, and then the soaked grafted product is filtered out and dried at 80°C and vacuum degree -0.1 MPa for 12 h to obtain the cotton-based room temperature phosphorescent material M6.
[0047] Example 7 Preparation of cotton-based room temperature phosphorescent material M7 The preparation method of this embodiment is the same as that of Example 5, with the only difference being that after obtaining the grafted product, the grafted product is subjected to silanol grafting treatment. The specific operation process is as follows: 5 g of n-octyltriethoxysilane is added to a mixture of 10 ml of ethanol and water (the volume ratio of ethanol to water is 9:1), hydrolyzed to form silanol, and then 0.1 g of the grafted product is added to react for 2 hours, and finally the grafted product after the reaction is filtered out and dried at 80°C and vacuum degree -0.1 MPa for 12 hours to obtain the cotton-based room temperature phosphorescent material M7.
[0048] Experimental Example 1 Optical properties test of cotton-based room temperature phosphorescent materials The optical properties of the cotton-based room temperature phosphorescent materials M1-M5 prepared in the above examples were tested, wherein the room temperature phosphorescence spectra were measured using a F-4600 spectrophotometer produced by Hitachi, and the phosphorescence lifetime was measured using a steady-state transient fluorescence spectrometer (Fluorolog-3-Tau and deltaflex). The results are shown in Table 1 below. The fluorescence and phosphorescence spectra of M1 to M5 are shown in Table 1 below. Figures 1 to 5 shown.
[0049] Table 1
[0050] The structural characterization analysis of absorbent cotton, modified cotton and M5 was carried out. Figure 6 As shown, where: Figure a shows the infrared spectra of different components and the subtraction spectra of M5 and modified cotton, 3600-3150cm -1 is the stretching vibration peak of hydroxyl, 3000-2800cm -1 is the stretching vibration peak of CH, 1050-950cm -1 is the stretching vibration peak of CO. It can be seen that M5 is at 1430-1310cm -1The absorption peak in the range is strong, proving that a large number of BO bonds are formed between the phenylboronic acid chromophore and the absorbent cotton. From the difference subtraction spectrum, it can be seen that the small molecule is successfully attached to the cotton.
[0051] Figure b is the X-ray diffraction spectrum of absorbent cotton and modified cotton. By comparing the XRD spectrum of modified cotton, it can be seen that the absorbent cotton only has an amorphous broad peak caused by the polymer, while the modified cotton has a finer peak structure, indicating that the redox modification has changed the crystalline structure of the cotton and formed a harder microenvironment.
[0052] Figure c is the X-ray electron energy spectrum carbon spectrum, and Figure d is the X-ray electron energy spectrum boron spectrum. The XPS spectrum shows that the binding energies of the COB covalent bond and the BO covalent bond are 289.3 eV and 192.9 eV, respectively, indicating that the grafting reaction was successfully carried out.
[0053] In addition, scanning electron microscopy observations of absorbent cotton and modified cotton were performed, see Figure 7 Figure a and Figure b show that the grafting reaction did not change the fiber structure of the absorbent cotton. M5 was made into ink (100 mg M5 was dissolved in 2 ml deionized water), and was written with a brush and injected with a syringe on the gauze. The gauze was exposed to natural light, 365 nm ultraviolet light, and 254 nm ultraviolet light for 2 seconds and then turned off. Figure 7 As shown in Figures c to h, it can be seen that after irradiation with 254nm UV light for 2s, afterglow emission was observed after turning off the UV light.
[0054] Fig.10 The phosphorescence spectra of M1 under different excitation wavelengths. It can be observed that as the excitation wavelength increases, the spectrum gradually red-shifts.
[0055] Experimental Example 2 Waterproof performance test of cotton-based room temperature phosphorescent materials Figure 8 These are the phosphorescence emission spectra of M2 at the beginning, after water vapor fumigation for 5 minutes, and after drying in a 100°C drying oven for 2 minutes and 4 minutes. It can be observed that the phosphorescence intensity of M2 decreases after humidification and gradually recovers after drying.
[0056] Fig. 9 The phosphorescence emission spectra of the waterproof control materials are shown in Figure a, M6 and M6 soaked in water, B and M7 soaked in water, and C and M5 soaked in water. It can be observed that the phosphorescence of M5 basically disappears after being soaked in deionized water, while M6 soaked in amino silicone oil and M7 grafted with silanol still retain some phosphorescence emission.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a room temperature phosphorescent material based on cotton, characterized in that: The following steps are involved: The absorbent cotton and the phenylboronic acid derivative are subjected to a grafting reaction to obtain a grafted product.
2. The method for preparing the cotton-based room temperature phosphorescent material according to claim 1, characterized in that: The phenylboronic acid derivative is selected from any one of 4-carboxyphenylboronic acid, 4,4'-biphenyldiboronic acid, 4-biphenylboronic acid and 4'-bromo-4-biphenylboronic acid.
3. The method for preparing a cotton-based room temperature phosphorescent material according to claim 1, characterized in that: The operation process of the grafting reaction is: immersing absorbent cotton in deionized water, adding a tetrahydrofuran solution of a phenylboronic acid derivative, then adding ammonia water, and then stirring at 80° C. for 1 hour, and finally filtering and drying to obtain the room temperature phosphorescent material.
4. The method for preparing a cotton-based room temperature phosphorescent material according to claim 1, 2 or 3, characterized in that: Before the grafting reaction, the absorbent cotton is subjected to oxidation treatment and reduction treatment in sequence.
5. The method for preparing the cotton-based room temperature phosphorescent material according to claim 4, characterized in that: The operation process of the oxidation treatment is: adding absorbent cotton and sodium periodate into deionized water, reacting at 60° C. in the dark for 10 hours, then adding ethylene glycol to stop the reaction, and finally dialyzing, filtering and drying.
6. The method for preparing the cotton-based room temperature phosphorescent material according to claim 5, characterized in that: The reduction treatment process is as follows: adding the oxidized absorbent cotton and sodium borohydride into deionized water, stirring at room temperature for 4 hours, and finally dialyzing, centrifuging, and drying.
7. The method for preparing a cotton-based room temperature phosphorescent material according to claim 1, 2 or 3, characterized in that: After the grafted product is obtained, the grafted product is subjected to silicone oil adsorption or silanol grafting treatment.
8. The method for preparing the cotton-based room temperature phosphorescent material according to claim 7, characterized in that: The operation process of silicone oil adsorption is: soaking the grafted product in amino silicone oil for 2 hours, and then taking it out for drying; The operation process of the silanol grafting treatment is: adding n-octyltriethoxysilane to a mixture of ethanol and water, hydrolyzing to form silanol, then adding the grafted product to react for 2 hours, and finally taking it out for heating and drying treatment.
9. A cotton-based room temperature phosphorescent material, characterized in that: Prepared according to the preparation method as described in any one of claims 1 to 8.
10. Use of the cotton-based room temperature phosphorescent material according to claim 9 in the preparation of ink or coating.
Citation Information
Patent Citations
Cellulose fiber and method for producing cellulose fiber
CN108505333A
Preparation method of flexible electromagnetic shielding fabric
CN114855443A
Dual-emission room-temperature phosphorescent material as well as preparation method and application thereof
CN115851267A
Organic room-temperature phosphorescent material as well as preparation method and application thereof
CN116376200A